Messy methods: Making sense of participatory research with young people in PE and sport. (August 2021) - Fitzgerald, Hayley; Stride, Annette; Enright, Eimear
Participatory research with young people has become an approach increasingly adopted by researchers within PE and sport. In this paper, we draw on our research diaries to collectively reflect on our experiences of attempting to work in participatory ways. Although we each work with different young people and have adopted differing participatory approaches, there are similarities in our research experiences. This includes recurring accounts of 'muddling through' and messiness occupying our reflections. We are also struck by the absence of concern within the literature to reveal the messiness of research. In light of our shared musings about participatory research with different young people, this paper offers some preliminary thoughts about our experiences of dealing with this messiness. We take as our focus the increasing concerns to support rights-based research that advocates inclusion, participation and empowerment, and draw on our research to explore how these features were worked towards. In these discussions we are open about the limitations of the research, challenges encountered and the resultant messiness arising. Our conclusion turns to what it might mean if researchers were more transparent about the usually unpredictable, messy and confusing situations that arise in the practice of doing participatory research with young people.